Pengaruh Popularitas Proyek dan Kualitas Informasi Proyek pada Kampanye Crowdfunding - Setiawan Mandala Putra; Fitriah Dwi Susilowati (Universitas Medan Area, 2020)
This study aims to examine project popularity and project information quality on the emotions felt by potential donors, as well as how these emotions can affect the trust and intention of donating potential donors on the crowdfunding platform. Data were collected through questionnaires on 130 undergraduate students in Surabaya, Indonesia. The participants have been actively using the internet and are aware of the crowdfunding platform itself. Through SEM analysis (PLS), the results show that project popularity and project information quality have a positive effect on positive emotion and have a negative effect on negative emotion. Furthermore, positive emotion has a positive effect on trust and negative emotion has a negative effect on trust. In the end, trust has a positive effect on the intention to donate. This study supports and extends the implementation of the stimulus-organismresponse (S-O-R) theory in the crowdfunding industry context. This study states that the intention to donate can be influenced by the trust of potential donors where their trust can be influenced by the emotions they feel and the emotions they feel can be influenced by the popularity of the project and the quality of information on a project.